Differences in loaded and unloaded vertical jumping ability and sprinting performance between brazilian elite under-20 and senior soccer players - Loturco, I.; Kobal, R.; Gil, S.; Pivetti, B.; Kitamura, K.; Pereira, L. A.; Cavinato Cal Abad, C.; Nakamura, F. Y. (American Journal of Sports Science, 2014)
The aim of this study was to compare performance in sprint, change of direction speed, vertical jump and jump squat tests between elite soccer players from two different age categories (i.e., under-20 and senior players) from the same soccer club. Players performed sprints (average velocity at 5, 10 and 20 m), zig-zag change of direction speed (COD speed), squat and countermovement jump tests and loaded jump squats to obtain the maximum mean propulsive power (MPP) value. Senior players performed better in absolute MPP, while the relative MPP (W/kg) was higher in the U-20 players. Moreover, except for COD speed and average velocity from zero to 5 m (VEL 5 m), the senior soccer players presented superior performance in all tested variables (SJ, CMJ, VEL 10 m, VEL 20 m). In conclusion, most neuromuscular variables improve during the transition from the end of adolescence to the mature phase. However, to enhance the power abilities and sprinting capacity over very short-distances of senior soccer players, soccer fitness coaches are encouraged to increase the frequency and volume of strength/power training during the competitive season.